A Comprehensive Analysis of Fibroblast Growth Factor Receptor 2b Signaling on Epithelial Tip Progenitor Cells During Early Mouse Lung Branching Morphogenesis - Matthew R. Jones; Matthew R. Jones; Salma Dilai; Arun Lingampally; Cho-Ming Chao; Cho-Ming Chao; Soula Danopoulos; Gianni Carraro; Regina Mukhametshina; Jochen Wilhelm; Eveline Baumgart-Vogt; Denise Al Alam; et al. (Frontiers in Genetics, 2019)
This study demonstrates that FGF10/FGFR2b signaling on distal epithelial progenitor cells, via ß-catenin/EP300, controls, through a comprehensive set of developmental genes, morphogenesis, and differentiation. Fibroblast growth factor (FGF) 10 signaling through FGF receptor 2b (FGFR2b) is mandatory during early lung development as the deletion of either the ligand or the receptor leads to lung agenesis. However, this drastic phenotype previously hampered characterization of the primary biological activities, immediate downstream targets and mechanisms of action. Through the use of a dominant negative transgenic mouse model (Rosa26rtTA; tet(o)sFgfr2b), we conditionally inhibited FGF10 signaling in vivo in E12.5 embryonic lungs via doxycycline IP injection to pregnant females, and in vitro by culturing control and experimental lungs with doxycycline. The impact on branching morphogenesis 9 h after doxycycline administration was analyzed by morphometry, fluorescence and electron microscopy. Gene arrays at 6 and 9 h following doxycycline administration were carried out. The relationship between FGF10 and ß-catenin signaling was also analyzed through in vitro experiments using IQ1, a pharmacological inhibitor of ß-catenin/EP300 transcriptional activity. Loss of FGF10 signaling did not impact proliferation or survival, but affected both adherens junctions (up-regulation of E-cadherin), and basement membrane organization (increased laminin). Gene arrays identified multiple direct targets of FGF10, including main transcription factors. Immunofluorescence showed a down-regulation of the distal epithelial marker SOX9 and mis-expression distally of the proximal marker SOX2. Staining for the transcriptionally-active form of ß-catenin showed a reduction in experimental vs. control lungs. In vitro experiments using IQ1 phenocopied the impacts of blocking FGF10. This study demonstrates that FGF10/FGFR2b signaling on distal epithelial progenitor cells via ß-catenin/EP300 controls, through a comprehensive set of developmental genes, cell adhesion, and differentiation.